Influence of Insecticide Application on Pollinators and Predatory Arthropods in Watermelon Agroecosystem - , Archana, B. R., Kishor Pujar, Chethan, T., Kavya, M. Hiremath; Godavari, Arpitha K.C.; Manjula, Harish Varma, M. (Archives of Current Research International, 2024)
This study, conducted from January to April 2021 in Kandavara village, Karnataka, examined the effects of various insecticides on honeybees, spiders, and coccinellids in watermelon crops. Using a randomized complete block design, watermelon plants were treated with insecticides when pest populations reached economic thresholds. Honeybee foraging activity and populations of spiders and coccinellids were monitored before treatment and at 3,7 and 10 days post-application. Results showed that untreated control plots consistently had the highest activity of all beneficial insects. Among the insecticides tested, Spinosad 45 SC was the least harmful, with relatively higher levels of honeybee and natural enemy activity. In contrast, Imidacloprid 17.8 SL and Acephate 75 SP were the most detrimental, resulting in significantly lower activity levels for honeybees, spiders, and coccinellids. These findings highlight the importance of selecting insecticides that minimize harm to beneficial insects, emphasizing the need for integrated pest management practices that balance effective pest control with the preservation of essential ecosystem services.